Research progress on multidimensional intervention strategies for hyperuricemia: Western medicine, Traditional Chinese Medicine, and emerging therapies - Li, Xinze; Chen, Zilong; Zhang, Yanzhao; Fan, Chunyang; Chen, Lulu; Xu, Xiangman; Chang, Jianying; Qiang, Wei; Jiang, Hongwei; Liu, Chuanxin (Frontiers in Endocrinology, 2025)
Hyperuricemia is a metabolic disease caused by purine metabolism disorders. In recent years, its incidence has been increasing year by year and showing a trend of rejuvenation. It is closely associated with various health issues such as gout, kidney damage, and cardiovascular diseases. Therefore, standardizing and updating its treatment strategies holds significant clinical importance. This article systematically reviews the current various intervention methods and research status for the treatment of hyperuricemia: In the field of Western medicine, it deeply analyzes the efficacy, mechanism of action, and clinical limitations of drugs that promote uric acid excretion (such as benzbromarone and dotinurad), drugs that inhibit uric acid synthesis (such as allopurinol, febuxostat, and topiroxostat), and drugs that promote uric acid hydrolysis (such as pegloticase and rasburicase). It focuses on elaborating the research breakthroughs of URAT1 inhibitor derivatives and the new drug SHR4640. In the field of Traditional Chinese Medicine (TCM), from three aspects of single-herb monomers, compound prescriptions, and external treatment methods, it reveals their advantages in reducing uric acid through multiple mechanisms, including inhibiting xanthine oxidase (XOD), regulating uric acid transporters such as URAT1, GLUT9, and OATs, and improving intestinal homeostasis, with particular emphasis on the structure-activity relationship of flavonoids. At the same time, it details the action pathways and clinical evidence of emerging therapies such as SGLT2 inhibitors, the GLP-1/GCG dual-receptor agonist Mazdutide, probiotics, and washed microbiota transplantation (WMT). By summarizing mechanistic insights, clinical progress, and translational prospects, this review aims to inform the development of individualized and integrative therapeutic strategies for hyperuricemia.